Robust Fabrication of Nonstick, Noncorrosive, Conductive Graphene‐Coated Liquid Metal Droplets for Droplet‐Based, Floating Electrodes. (15th January 2018) - Chen, Yuzhen; Zhou, Tingjiao; Li, Yaoyao; Zhu, Lifei; Handschuh‐Wang, Stephan; Zhu, Deyong; Zhou, Xiaohu; Liu, Zhou; Gan, Tiansheng; Zhou, Xuechang
Abstract: Nontoxic liquid metals (conductive materials in a liquid state at room temperature) are an emerging class of materials for applications ranging from soft electronics and robotics to medical therapy and energy devices. Their sticky and corrosive properties, however, are becoming more of a critical concern for circuits and devices containing other metals as these are easily destroyed or contaminated by the liquid metals. Herein, a feasible method for fabricating highly conductive graphene‐coated liquid metal (GLM) droplets is reported and their application as nonstick, noncorrosive, movable, soft contacts for electrical circuits is demonstrated. The as‐prepared GLM droplets consist of a liquid‐phase soft core of liquid metal and a slippery outer layer of graphene sheets. These structures address the issue of simultaneous control of the wettability and conductivity of a soft electronic contact by combining extraordinary properties, i.e., nonstick, noncorrosive, yet exhibiting high electronic conductivity while in contact with metal substrates, e.g., Au, Cu, Ag, and Ni. As proof‐of‐concept, the as‐prepared GLM droplets are demonstrated as floating electrodes for movable, recyclable electronic soft contacts in electrical circuits. Abstract : Highly conductive graphene‐coated liquid metal (GLM) droplets are fabricated and used as nonstick, noncorrosive, movable, soft electric contacts for droplet‐based soft electronics. The GLM droplets consist of a liquid‐phase soft core of liquid metal and a slippery outer layer of graphene sheets, which well addresses the issue of simultaneously controlling the wettability and conductivity of liquid metal droplets.